ANALISIS KESADARAN HUKUM MASYARAKAT PADA PERATURAN PEMERINTAH NOMOR 18 TAHUN 2021 (STUDI KASUS KEPATUHAN MASYARAKAT KELURAHAN SENYERANG KABUPATEN TANJUNG JABUNG BARAT) - M. Arya; Muhammad Ichsan; Heri Usmanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the gap (das sollen and das sein) between national land rights registration regulations and the empirical reality on the ground. Government Regulation (PP) Number 18 of 2021 requires upgrading the legal status of land from traditional/customary documents (such as sporadic, girik, or letter C) to Freehold Certificates (SHM) for legal certainty. However, data from the Land Office indicates that the level of non-compliance among residents in Senyerang Village remains very high, reaching 73.84% (1,078 households). This study aims to analyze the legal awareness and compliance of the Senyerang Village community regarding PP Number 18 of 2021 and identify factors influencing legal awareness and compliance in implementing the regulation.The method used in this study is a qualitative descriptive approach with empirical/field legal research. Informants were selected using a purposive sampling technique, consisting of the Senyerang Village Head (key informant), community leaders (additional informants), and local residents (main informants). Data collection techniques included observation, unstructured interviews, and documentation. Data validity was tested using technical triangulation, source triangulation, and time triangulation. Data analysis techniques applied included data reduction, data presentation, and conclusion drawing.The results of the study indicate that the level of legal awareness of Government Regulation No. 18 of 2021 among the Senyerang Village community remains low and suboptimal. Based on indicators of legal knowledge and understanding, residents are only aware of the general land registration regulations but do not understand the procedures, rights, obligations, or legal consequences. Based on indicators of legal attitudes, residents respond positively to the importance of land certification, but their actual behavior is inconsistent due to the perceived complexity, cost, and lack of urgency in their practice. Factors influencing and hindering this level of legal awareness and compliance include residents' limited economic conditions, low levels of formal education, a lack of internal community willingness to learn the regulations, and suboptimal service delivery, guidance, and direct outreach from village government officials and relevant land agencies.